Correlated-Photon Secured Imaging by Iterative Phase Retrieval Using Axially-Varying Distances - Chen, Wen (IEEE photonics technology letters, 2016)
Correlated-photon imaging (also called ghost imaging) has attracted much attention in various fields, and its characteristics, such as single-pixel detection, have been extensively explored. In this letter, correlated-photon imaging is presented by using iterative phase retrieval with axially varying distances for optical encryption. A series of phase-only masks are iteratively extracted by modulating the pre-generated random intensity-only maps, and propagation distances are axially varied in a random manner. It is illustrated that the setup parameter can be applied as one of significant keys rather than just complementary one, and the iterative phase retrieval algorithm is applied to flexibly generate phase-only masks for the encoding.